Analisis Tingkat Kepuasan Peserta Didik Terhadap Pelaksanaan Program Pembinaan Kreativitas di MI Muhammadiyah 02 Kabupaten Sorong - Niken Utami (Program Studi Pendidikan Guru Madrasah Ibtidaiyah Institut Agama Islam Negeri Sorong, 2025)
This research aims to analyze students' satisfaction levels regarding the implementation of creativity development programs as part of the Pancasila Student Profile Reinforcement Project (P5) at MI Muhammadiyah 02, Sorong Regency. Employing a descriptive quantitative approach, the study involved 120 students from grades I to VI selected through stratified random sampling. Data were collected using a Likert-scale questionnaire that assessed five indicators: student engagement and activeness, relevance to students’ interests and talents, teacher or facilitator support, development of Pancasila Student Profile competencies, and enjoyable learning experience. The results indicated a high overall satisfaction score of 4.26 (85%), categorized as “very satisfied.” The highest-rated indicator was “teacher or facilitator support” (88%), while “student engagement and activeness” scored the lowest (78%), though still within the “satisfied” category. These findings suggest that the program was well-received and successfully supported students’ creativity and character development. However, there remains a need to enhance students' active involvement in project activities. This study is expected to serve as a reference for future research and contribute to the development of P5-based programs in elementary Islamic educational institutions.